Bond strength and stability of 3 luting systems on a zirconia-dentin complex - (:unkn) unknown (Academy of General Dentistry, 2013)
This study compared the bond strength and stability of 3 different luting systems to a zirconia ceramic crown. Sixty cylinders of zirconia ceramic were cemented to flat dentin surfaces of extracted human teeth, using 3 different luting agents (n = 20): a glass ionomer (GI) cement, a resin-modified glass ionomer (RMGI) cement, and a resin cement containing 10-methacryloyloxydecyl dihydrogen phosphate (MDP). The specimens from each cement group were then divided into 2 subgroups (n = 10). Three subgroups (1 from each cement) were selected to test shear bond strength (SBS) immediately before an aging process of thermocycling and water storage, the remaining 3 subgroups were tested for SBS after the aging process. The aging process affected the bond strength of the MDP and RMGI cements. The MDP cement demonstrated superior bond strength compared to the GI and RMGI cements; the GI cement consistently had the lowest bond strength. The RMGI cement had higher cohesive failures at cement (70%), while the GI and the MDP cements had higher percentages of adhesive failure at the ceramic-cement interface (70% and 100%, respectively). The MDP cement promoted better adhesion between dentin and the zirconia ceramic.